2014
DOI: 10.1159/000366386
|View full text |Cite
|
Sign up to set email alerts
|

Distinct DNA Methylomes of Human Placentas Between Pre-Eclampsia and Gestational Diabetes Mellitus

Abstract: Background: The placenta acts not only as a conduit of nutrient and waste exchange between mother and developing fetus but also functions as a regulator of the intrauterine environment. Pre-eclampsia (PE) and gestational diabetes mellitus (GDM) are leading causes of complications during pregnancy. Pathophysiologies show that they are associated with one another. Epigenetics provides a link between environmental factors that have previously been linked to poor pregnancy outcomes and fetal programming. Methods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 40 publications
2
46
1
1
Order By: Relevance
“…MiRNA is involved in a variety of cellular processes, for example, proliferation, differentiation, apoptosis and development. Aberrant expression of miRNA has been detected in many diseases, such as cancer, type 2 diabetes as well as cardiovascular neurological and autoimmune diseases [7][8][9][10]. Previous studies have suggested that miRNAs are involved in GDM [11].…”
Section: Introductionmentioning
confidence: 99%
“…MiRNA is involved in a variety of cellular processes, for example, proliferation, differentiation, apoptosis and development. Aberrant expression of miRNA has been detected in many diseases, such as cancer, type 2 diabetes as well as cardiovascular neurological and autoimmune diseases [7][8][9][10]. Previous studies have suggested that miRNAs are involved in GDM [11].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, sPE is an important iatrogenic cause of prematurity. Recently the placenta has become a focus of researchers' attention, as early-onset PE is generally considered as a primarily placental disease [3][4][5]. Syncytiotrophoblast extracellular vesicles (STBM) are continuously shed and secreted from the placental syncytium into the maternal circulation in normal pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic mechanisms are not only important in early phases of pregnancy but throughout gestation [131,132]. Current literature suggests that epigenetic modifications acquired during early developmental phases can be permanent [133].…”
Section: Epigeneticsmentioning
confidence: 99%